Developing English Language Teaching Researchers’ Oral Argumentative Skills Through Webinar - Mohammad Abu El-Magd Mohammad Abu El-Magd (Maǧallaẗ Kulliyyaẗ Al-Tarbiyyaẗ - Ǧamiʿaẗ Būr Saʿīd, 2017)
This research aimed at developing the oral argumentative skills of the ELT researchers at Ismailia Faculty of Education in order to help them present their work in a way that convinces the opposing side and leads to a fruitful discussion. TEFL topics were taken from their M.Ed. and PhD researches for presentation and oral discussion through webinar sessions in order to determine how far webinar was effective on developing their oral argumentation. The subjects were eight ELT researchers from Ismailia Faculty of Education in Suez Canal University (SCU). The research design was a combination between two methods: the quasi-experimental method which was used for statistical testing of the hypothesis as well as the descriptive method that was used to find out how much progress had been achieved through the sequence of the eight webinar sessions. The measurement tool was an analytic rating scale for oral argumentation rubrics developed by the researcher. The findings revealed that webinar had a high positive effect on developing the ELT researchers’ oral argumentative skills.